Light-driven dancing of nematic colloids in fractional skyrmions and bimerons - Zhawure Asilehan; Wentao Tang; Jing Zhang; Zijun Chen; Ruijie Wang; Qingtian Shi; Ganlin Song; Jinghua Jiang; Rui Zhang; Chenhui Peng (Nature Communications)
Abstract Materials with full and fractional skyrmions are important for fundamental studies and can be applied as information carriers for applications in spintronics or skyrmionics. However, creation, direct optical observation and manipulation of different skyrmion textures remain challenging. Besides, how the transformation of skyrmion textures directs the dynamics of colloids is not well understood. Here, we use experiments, simulations and theory to demonstrate that fractional skyrmion and bimeron strings can be created in a nematic liquid crystal (LC) through incompatible interfaced topological patterns. Moreover, distinct topological profiles are realized in the same skyrmion string loop. The light-actuated transformations of fractional skyrmion textures in both straight and loop geometry drive colloidal assemblies to exhibit exotic dynamic behaviors. Finally, fractional skyrmions with arbitrary shapes can be used as templates for a variety of exquisite colloidal assemblies. This work provides opportunities for designing new smart material to control self-assembly and transport of colloids.